Strategic Innovation in Crisis Management Converting into Opportunity: A Case Study of the Dubai Government - Kashri, Hanan (Journal of Public Policy and Administration, 2024)
Purpose: The conventional crisis management framework, which is characterized by predetermined protocols and reactive actions, has proven ineffective in the face of the complex circumstances of today. The Dubai Government has acknowledged this and adopted a paradigm shift toward strategic innovation, marking a break from the status quo and a readiness to accept uncertainty as a necessary step toward advancement. The strategic innovation framework used by the Dubai Government's crisis management plan will be thoroughly examined in this research. The purpose of the study is to elucidate the guiding principles that have placed this forward-thinking organization at the forefront of crisis resilience via the prism of this progressive organization. It aims to understand the mechanics of crisis management and to draw general lessons that may be used in other organizational contexts by probing the methodology, technologies, and cultural shifts that support this novel approach (Alketbi, del Rio and Fernández, 2022). Methodology: To encapsulate, this research utilizes a qualitative triangulation approach that focuses on the relationship between strategic innovation and crisis management, specifically examining the Dubai Government. By combining qualitative interviews, quantitative surveys, and content analysis, the study provides a comprehensive view of the topic, enabling a thorough investigation of the research questions and objectives. Findings: Based on prior research and global trends, the main finding is to understand the Dubai Government who has seamlessly merged innovation into its crisis management tactics. The focus is on how the Dubai Government integrates advanced technological tools and fosters a culture where challenges are viewed as opportunities for growth. For instance, the adoption of AI-based predictive analytics in crisis anticipation and response is a testament to this innovative approach. Unique Contribution to Theory, Practice and Policy: The study anticipates that these practices not only enhance crisis management effectiveness but also serve as a model for other organizations globally.